KAJIAN ATRAKSI AMENITAS DAN AKSESIBILITAS UNTUK PENGEMBANGAN WISATA BAHARI PULAU SENOA - Lutfi, Marhafiz (JURNAL NASIONAL PARIWISATA, 2013)
This research is aimed to indentify the tourism attraction condition, the amenity and the accessibility of tourist destination of Senoa Island in Natuna and its compatibility with touristic activities that can be developed, and to identify tourist perception from them who visited Natuna. Therefore, we hope that we could arrange appropriate strategy for the tourism development.Â The method used is a descriptive analysis on the condition of tourist attractions, the amenities and the accessibilities with field observation to measure the visual quality. To assess the condition and properness of the amenities and the accessibilities, we implement field observation, secondary data analysis on the number of facilities and infrastructures and its properness assessed by tourist perception from them who visited Natuna. Â From this research result, we found that Senoa Island has potential tourist attractions that need to be developed as marine tourism destination. However, they have deficient amenity and inadequate accessibility. Most of the tourists are local. This is because the location is relatively far from the tourist residence area. In general, the perception on these tourism attractions is excellent. Therefore, development strategy should be developed by prioritizing tourism development, improving role of the businesses and an active participation of the society to maximize the tourism existence and potential in Senoa Island.Â